A Pattern-based Imaging Approach to Pediatric Jaw Lesions - Sahu, Biswanath; Anand, Rama; Kumar, Sandeep; Solanki, Ravi Shankar; Mehra, Pravesh; Jain, Manjula (Indian Journal of Radiology and Imaging, 2021)
Jaw lesions in the pediatric population, although infrequently encountered in clinical practice, can cause functional impairment and cosmetic disfiguring. It is further complicated by the difficulty in diagnosis due to complex anatomy and facial developmental process during infancy and childhood. Intraosseous pediatric jaw lesions may vary from odontogenic to nonodontogenic types with nonspecific clinical features in most cases. They deserve careful attention by a systematic approach to provide a relevant diagnosis or differential diagnosis for timely management. Imaging plays a major role in diagnosis with orthopantomograph being the foremost investigation, followed by cross-sectional imaging, essentially computed tomography as a problem-solving tool. This article highlights the imaging spectrum of various jaw lesions in the pediatric population with a pattern-based approach for radiological diagnosis.
Keywords: computed tomography; jaw lesion; nonodontogenic; odontogenic; orthopantomograph; pediatric